2011
DOI: 10.3113/fai.2011.0659
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Moderate to Severe Coronal Plane Deformity with the STAR™ Ankle Prosthesis

Abstract: Correction of moderate to severe coronal plane deformity with the STAR prosthesis was achievable with only soft-tissue balancing procedures with predictable results especially for deformities less than 25 degrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 9 publications
0
44
1
Order By: Relevance
“…With use of this reasoning, coronal plane deformity exceeding 15°of varus or valgus often has been cited as a contraindication to total ankle replacement [26][27][28] . Prohibiting this population of patients from receiving a total ankle replacement eliminates a large proportion of those who might benefit from this procedure.…”
mentioning
confidence: 99%
“…With use of this reasoning, coronal plane deformity exceeding 15°of varus or valgus often has been cited as a contraindication to total ankle replacement [26][27][28] . Prohibiting this population of patients from receiving a total ankle replacement eliminates a large proportion of those who might benefit from this procedure.…”
mentioning
confidence: 99%
“…Interestingly, Reddy and colleagues 24 showed that preoperative varus deformity of greater than 10 in 43 ankles, treated with the Scandinavian TAR (Waldemar Link, Hamburg, Germany/Small Bone Innovations, Inc, Morrisville, PA/Stryker Orthopedics, Mahwah, NJ) were corrected with soft tissue procedures only, without performing osteotomies. However, 3 ankles with deformity greater than 25 failed.…”
Section: Clinical Results In the Literaturementioning
confidence: 97%
“…8,9,[19][20][21][22][23][24][25][26] One cannot isolate many studies reporting on outcomes of TARs combined with osteotomies, as these procedures are part of the whole spectrum of surgery performed for ankles with greater than 10 coronal plane deformity. Doets and colleagues 20 reported on his series of 15 TARs in varus ankles, requiring a medial malleolar lengthening osteotomy.…”
Section: Clinical Results In the Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…Moderate to severe coronal ankle malalignment has been considered a con- n guest editorial traindication for TAA and is currently a heavily debated topic. 13,14 New investigations are demonstrating better predictability for more significant coronal plane deformities through a structured and thoughtful approach, occasionally requiring staged reconstructions. 15 Expanded indications to include younger patients with increasing deformity have been recently implemented with success.…”
mentioning
confidence: 99%